Value chain analysis of sunflower in coastal areas of Amtali upazila of Barguna district: Sunflower value chain analysis - Hossain, Mohammad Ismail; Afroz, Shaon; Das, Mahanambrota; Haque, Md. Mojammel; Islam, M. Serajul; Camacho, Lilly Lim- (Journal of the Bangladesh Agricultural University, 2019)
Sunflower is an important oil seed crop which is well fitted in Robi season of the coastal areas of Bangladesh. This study focused on sunflower value chain map, value addition, value chain governance and institutional linkages, and stakeholders and their roles and responsibilities in value adding process of sunflower. A total of 60 respondents were interviewed by using pretested questionnaire. A combination of purposive and snowball sampling techniques was used to select the respondents. Descriptive analytical technique was used to achieve the objectives. The study found that farmers were hardly engaged in sunflower marketing activities. The value chain map comprised of collectors/assemblers, processors, wholesalers and retailers. On an average, total costs (production and marketing) incurred by the farmers were Tk. 11,986.30/acre (100 decimals) of sunflower. Assemblers received a total gross margin of Tk. 588/100 kg of sunflower seeds. At wholesale node the total gross margin was found to be Tk. 209/100kg of sunflower seeds. It was observed that processor received gross margin of Tk. 878. The processors were the pivotal point for the sunflower oil in the study area. The findings revealed that 40% of the total sunflower seed productions were sold by farmers to chain actors in while the remaining 60% was left for own consumption. It was also found that there was certain arrangements of producers and traders in case of production and marketing of sunflower. The main business challenge in sunflower production is scarcity of quality seed and the marketing challenge is fluctuation of prices. Thus, policy should be guided to supply quality seeds and maintain the stable price of sunflower. J. Bangladesh Agril. Univ. 17(2): 244–250, June 2019